Renewable Pathways to O-Decyl Hydroxylamine: Mild Thermal Hydrolysis of Gmelina arborea Leaves Using Barium Chloride - Haruna Ibrahim; Abubakar M. Ali; Mohammed Danlami Jibrin (Indonesian Journal of Green Chemistry, 2026)
O-Decyl hydroxylamine is a high-value nitrogen-functionalized intermediate with wide industrial relevance in fine chemicals, antioxidants, surfactants, and advanced material formulations. However, its conventional synthesis relies predominantly on petrochemical feedstocks, halogenated reagents, and multistep processes that raise concerns regarding sustainability, energy intensity, and environmental impact. In this study, a mild and sustainable barium chloride (BaCl2)-catalyzed thermal hydrolytic process is developed for the direct production of O-decyl hydroxylamine from Gmelina arborea leaf biomass, an abundant and underutilized lignocellulosic resource. The reaction was conducted in aqueous medium at atmospheric pressure over a temperature range of 60-90 °C and catalyst loadings of 0.5-1.0 wt%. Product formation was confirmed by GC-MS following derivatization, while process performance was evaluated through yield determination, reproducibility assessment, and rigorous statistical analysis. The results reveal a strong temperature-catalyst interaction governing product yield. Maximum yield (106.5 mg g⁻¹) with excellent reproducibility (CV < 5%) was achieved at 90 °C using 0.5 wt% BaCl2, whereas higher temperatures favoured lower catalyst loading. Two-sample t-tests, Welch’s t-test, and Tukey HSD post-hoc analysis confirmed that temperature exerts a more dominant influence than catalyst loading, with statistically significant differences observed under specific operating conditions (p < 0.05). The developed process operates under low-severity conditions, avoids hazardous reagents, and demonstrates high precision and robustness. Overall, this work establishes a statistically validated and energy-efficient pathway for producing O-decyl hydroxylamine directly from biomass, advancing sustainable chemical manufacturing and supporting the development of renewable, bio-based fine chemicals in alignment with SDGs 9 and 12.